(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
Since 2016, the studies on in vitro rearing Braconidae and Trichogrammatidae (B. habetor Say, B. greeni and T. pintoe, T. evanescens, T. chilonis) have been conducted successfully in Uzbekistan. For these parasites, cooking and the three main types of media were made from the hemolymph of the wax moth (G. melonnella) and cotton worm Helicoverpa armigera (Heliothis armigera), egg yolk, natural milk 10%. The simulated "host-eggs" and "larvae" are made of polyethylene or polypropylene semi spherical capsules, containing artificial diets, in which insectan pupal hemolymph is the main component. Mass production of in vitro reared Braconidae and Trichogrammatidae its utilization in the fields showed good effectiveness in controlling cotton bollworm